Gene-environment interplay in attention-deficit hyperactivity disorder and the importance of a develomental perspective - GILL, MICHAEL (The Royal College of Psychiatrists, 2007)
Attention-deficit hyperactivity disorder (ADHD) varies in its clinical presentation and course. Susceptibility gene variants for ADHD and associated antisocial behaviour are being identified with emerging evidence of gene-environment interaction. Genes and environmental factors that influence the origins of disorder are not necessarily the same as those that contribute to its course and outcome.
PUBLISHED
Keywords: Psychiatry